Public Spending and Outcomes: Does Governance Matter? - Rajkumar, Andrew Sunil; Swaroop, Vinaya (2012)
This paper studies the links between public spending, governance, and outcomes. We examine the role of governance--measured by the level of corruption and the quality of bureaucracy--in determining the efficacy of public spending in improving human development outcomes. Our analysis contributes to our understanding of the relationship between public spending, governance and outcomes, and helps explain the surprising result that public spending often does not yield the expected improvement in outcomes. We show empirically that the differences in the efficacy of public spending can be largely explained by the quality of governance. Public health spending lowers child mortality rates more in countries with good governance. Similarly, public spending on primary education becomes more effective in increasing primary education attainment in countries with good governance. More generally, public spending has virtually no impact on health and education outcomes in poorly governed countries. These findings have important implications for enhancing the development effectiveness of public spending. The lessons are particularly relevant for developing countries, where public spending on education and health is relatively low, and the state of governance is often poor.